2015
DOI: 10.1590/0100-67622015000200019
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Wood Drying Defect Scores: Specimen Testing X Analysis of Kiln-Dried Boards

Abstract: -It is important to develop drying technologies for Eucalyptus grandis lumber, which is one of the most planted species of this genus in Brazil and plays an important role as raw material for the wood industry. The general aim of this work was to assess the conventional kiln drying of juvenile wood of three clones of Eucalyptus grandis. The specific aims were to compare the behavior between: i) drying defects indicated by tests with wood specimens and conventional kiln-dried boards; and ii) physical properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…Table 5 shows the initial and final temperatures and the drying potential, which were estimated using Equation 4, Equation 5, Equation 6, and compares the UM and the SM in tests at 100 °C for clones 58 and GG100, respectively. IT and FT mean values in Table 5 are similar to those reported in the literature by Brandão et al (1989), Barbosa et al (2005), Eleotério et al (2015), Batista et al (2015), Kang et al (2015), Tari et al (2015), Phonetip et al (2018a) and Phonetip et al (2018b), in which IT ranged from 39 °C to 49 °C and FT ranged from 62 °C to 76 °C. However, the mean DP presented in Table 5 was lower to the related by these authors (ranged from 2,0 to 2,7), which may be a disadvantage regarding the drying time.…”
Section: Estimates Of Parameters Of Drying Schedulessupporting
confidence: 87%
See 3 more Smart Citations
“…Table 5 shows the initial and final temperatures and the drying potential, which were estimated using Equation 4, Equation 5, Equation 6, and compares the UM and the SM in tests at 100 °C for clones 58 and GG100, respectively. IT and FT mean values in Table 5 are similar to those reported in the literature by Brandão et al (1989), Barbosa et al (2005), Eleotério et al (2015), Batista et al (2015), Kang et al (2015), Tari et al (2015), Phonetip et al (2018a) and Phonetip et al (2018b), in which IT ranged from 39 °C to 49 °C and FT ranged from 62 °C to 76 °C. However, the mean DP presented in Table 5 was lower to the related by these authors (ranged from 2,0 to 2,7), which may be a disadvantage regarding the drying time.…”
Section: Estimates Of Parameters Of Drying Schedulessupporting
confidence: 87%
“…Those studies confirmed that developed drying schedules shortens times and reduces overall work. Some studies also confirmed the correlation between defects detected in wood samples during the drastic drying test and those detected in planks during kiln drying, while others did not (Batista et al 2015).…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations